The nightworld - Blaine, Jack (Harper, 2012)
Scraping by in classes, hanging out with his best friend Charlie, and trying to get a date with Lara Hanover--that was Nick Robbins's life. Survival was the last thing on his mind, but then a strange cloud appears over the city, blocking out the sun and casting the entire world in darkness.